Utility of Combined Assessment With 2- and 3-Dimensional Transesophageal Echocardiography for Acommissural Unicuspid Pulmonic Valve With Severe Pulmonic Valve Stenosis. Issue 8 (15th October 2018) - Kuroda, Masataka; Maeda, Takayasu; Usuda, Iwao; Mita, Norikatsu; Kagaya, Shin; Miyoshi, Sohtaro; Saito, Shigeru; Yamashiro, Masahito
Abstract : Supplemental Digital Content is available in the text.